Sticky ends in a self-assembling ABA triblock copolymer: the role of ureas in stimuli-responsive hydrogels. Issue 1 (28th November 2018) - Shafranek, Ryan T.; Leger, Joel D.; Zhang, Song; Khalil, Munira; Gu, Xiaodan; Nelson, Alshakim
Abstract : Directed self-assembly in polymeric hydrogels allows tunability of thermal response and viscoelastic properties. Abstract : Directing polymer self-assembly through noncovalent interactions is a powerful way to control the structure and function of nanoengineered materials. Dynamic hydrogen bonds are particularly useful for materials with structures that change over time or in response to specific stimuli. In the present work, we use the supramolecular association of urea moieties to manipulate the morphology, thermal response, and mechanical properties of soft polymeric hydrogels. Urea-terminated poly(isopropyl glycidyl ether)- b -poly(ethylene oxide)- b -poly(isopropyl glycidyl ether) ABA triblock copolymers were synthesized using controlled, anionic ring-opening polymerization and subsequent chain-end functionalization. Triblock copolymers with hydroxy end-groups were incapable of hydrogelation, while polymers terminated with meta -bis-urea motifs formed robust gels at room temperature. Rheometric analysis of the bulk gels, variable-temperature infrared spectroscopy (VT-IR), differential scanning calorimetry (DSC), and small-angle X-ray scattering (SAXS) confirmed the formation of structured hydrogels via association of the meta -bis-urea end-groups. Monourea end-groups did not result in the same regular structure as the meta -bis-urea. In future, the reported hydrogels could be useful for elastomeric, shape-morphing 3D-printed constructs, or as biomimetic scaffolds with precisely tailored porosity and mechanical properties.